69 THE EFFECT OF NARINGENIN (GRAPEFRUIT JUICE) AND ANTIARRHYTHMIC DRUGS ON IKr INHIBITION. (1st March 2006) - Lin, C.; Ke, X.; Cvetanovic, I.; Ranade, V.; Somberg, J. C.
Abstract : Grapefruit juice has been reported to cause significant QT prolongation in healthy volunteers. Naringenin (N), the principal flavonoid in grapefruit juice, has been identified as the most potent HERG channel blocker among several dietary flavonoids. In light of these reports, we thought that combining naringenin with Ikr-inhibiting antiarrhythmic drugs would increase IKr inhibition and possibly pose an increased health risk by increasing repolarization delay and ensuing arrhythmias. In this study, we investigated the effect of N combined with quinidine (Q) on IKr inhibition. The study was performed in an oocyte system with heterogeneously expressed human-ether-a-go-go-related gene (HERG) employing two electrodes voltage clamp technique for recording. The experiments were performed at room temperature. Doses of 10 μM and 100 μM N were found to inhibit HERG channel by 15 ± 4 and 40 ± 7%. Q at 1 and 10 μM caused 9 ± 1 and 39 ± 3% inhibition of HERG current. When 10 μM N was combined with 1 μM Q, 9 ± 3% current was blocked. HERG current was blocked by 29 ± 2% when 10 μM N was combined with 10 μM Q. N 100 μM combined with 1 μM Q and N 100 μM combined with 10 μM Q caused 21 ± 2 and 36 ± 2% inhibition in HERG current, respectively. Combining naringenin and quinidine does not show an additive effect but rather a diminution in IKr inhibition. Further studies on the interaction of N with other known IKr channel blockers are indicated.